EVALUATION OF THE CRYSTALLINITY OF BACTERIAL CELLULOSE PRODUCED FROM PINEAPPLE WASTE SOLUTION BY USING ACETOBACTER XYLINUM (ASEAN Engineering Journal, 2023)
Bacterial cellulose (BC) is a fermentative product of Acetobacter xylinum characterized by high purity and crystallinity of up to 80%. Due to its excellent physical and mechanical properties, bacterial cellulose is increasingly interested in research, especially in the study of applying BC in different fields. Although it is a potential direction, the large-scale production of BC still has certain limitations, mainly the fermentation medium's high cost. Therefore, this study used pineapple waste as a carbon source for BC fermentation. After investigating the influence of fermentation factors on BC yield, this study focused on evaluating the crystallinity of BC under different fermentation conditions. The X-ray diffraction technique was used to determine the crystallinity, while Scanning Electron Microscopy was used to assess the differentiation of the BC structure. The study results showed that, at different fermentation conditions of temperature (25–35°C), time (5–10 days), and bacterial concentration (5–15%), the bacterial cellulose crystallinity was significantly different and in the range of 40.6 % to 83.4 %. The optimum crystallinity of BC was recorded when the experiment was set up at the fermentation temperature of 30°C, 13 days of fermentation time, and bacterial concentration of 14%, with the BC crystallinity being 82.2%.